Violation of cyberlaws and computer ethics: the consequences and potential legal actions - Abdul Jalil, Juriah; Mohamed, Duryana (2010)
Good ethics and professionalism when using computer or Internet should be strictly observed and exercised. Failure to do so will result in violation of the laws and computer ethics. Consequently, not only the victim will suffer loss but also the country as a whole. It is known that, the borderless nature of the cyber world has encouraged many people to try and explore various types of cyber activities but that is not a passport for everybody to cross the border and ignored the laws and regulations. Although there are cyber laws to control and regulate these cyber activities cases of cyber attacks and invasion to privacy and safety are still rampant. Thus, this paper seeks to study the available laws governing computer users, cases that involve violation of cyber laws and computer ethics, the effect of violation of those laws on the victim and finally, the potential legal actions available tothe victim of cyber attacks according to the categories of the offences. References will be taken from various discussion on cyber and computer ethics as well as cases on cyber offences. In conclusion, the authors hope that this paper would be able to assist the victims to stand up for their rights by seeking the available remedies besides providing resources to lawyers and court officers in dealing with cases on cyber attacks, particularly in Malaysia.